Why do PAM projects fail?. Issue 9 (September 2019) - Walker, Paul
Abstract : Every computer operating system and business application needs certain user accounts to function. There's no getting away from that. Accounts with higher levels of permissions (often, but not limited to, administrator accounts) are often referred to as privileged accounts. And these privileged accounts have almost unlimited access across computer systems. As a result, anyone with access to these computer accounts also has access to highly sensitive company information and once these credentials are targeted, they can easily lead to a breach of a company's most valuable assets, from databases to social media and unstructured data.